Electrochemical sensor highly selective for lindane determination: a comparative study using three different a-MnO2 nanostructures - Anu Prathap, Mylamparambil Udayan (2016)
Here we describe a simple, highly reproducible ultra-sensitive electrochemical sensor for lindane based on a-MnO2 nanostructures. The results showed that the a-MnO2 nanostructures effectively catalyzed the electrochemical reduction of lindane. A good linearity was obtained in the range of 1.1 to 510 mM with a detection limit of 114 nM. The proposed lindane sensor was successfully employed for the determination of lindane in tap water samples with good recoveries. Negligible amperometric currents are observed in the control experiments using triclosan (T), chlorobenzene (CB), benzene (B), 1,3,5-trichlorobenzene (1,3,5-TCB), and 4-chlorobenzaldehyde (4-CBA), suggesting a sensing specificity to lindane. The proposed sensor also exhibited good stability and reproducibility for lindane determination.